2020
DOI: 10.1101/2020.09.18.304055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genes involved in cholesterol cascades are linked to brain connectivity in one third of autistic patients

Abstract: The large heterogeneity in the symptomatology and severity of autism spectrum disorder (ASD) is a major drawback for the design of effective therapies. Beyond behavioral phenotypes, subtype stratification strategies that can be applied to large populations are needed, these combining different neurobiological characteristics and based on the large-scale organization of the human brain, as well as neurogenetic fingerprints. Here, we make use of ABIDE, the largest publicly available database of functional neuroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…This theory assumes an inefficient interregional brain connectivity across the cerebral cortex that results in abnormal information integration at psychological and neural levels in autistic brains and may also explain diverse impairments in social symptoms (Just et al, 2004; Schipul, Keller, & Just, 2011). Other studies also revealed that the overall connectivity class in ASD is highly heterogeneous, and a combination of hyper‐ and hypo‐connectivity seems to coexist across different subtypes of ASD (Maximo & Kana, 2019; Rasero, Jimenez‐Marin, Diez, Hasan, & Cortes, 2020; Yerys et al, 2017) and trajectories of neural development (C. He et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This theory assumes an inefficient interregional brain connectivity across the cerebral cortex that results in abnormal information integration at psychological and neural levels in autistic brains and may also explain diverse impairments in social symptoms (Just et al, 2004; Schipul, Keller, & Just, 2011). Other studies also revealed that the overall connectivity class in ASD is highly heterogeneous, and a combination of hyper‐ and hypo‐connectivity seems to coexist across different subtypes of ASD (Maximo & Kana, 2019; Rasero, Jimenez‐Marin, Diez, Hasan, & Cortes, 2020; Yerys et al, 2017) and trajectories of neural development (C. He et al, 2020).…”
Section: Discussionmentioning
confidence: 99%